Urinary infection in intensive care unit: indicators of procedure for prevention - Menegueti, Mayra Gonçalves; Martins, Maria Auxiliadora; Canini, Silvia Rita Marin da Silva; Filho, Aníbal Basile; Laus, Ana Maria (Rev Rene, 2012)
This descriptive study evaluated the predisposing factors for the occurrence of Urinary Tract Infection in critically ill patients hospitalized in an intensive care unit. An indicator was used to evaluate the conditions of maintenance of the indwelling vesical catheterization, consisting of five components. Data collection was performed daily during July and August 2007, through direct observation. Of the 471 observations, the item positioning the collection bag had 100% of adequacy, closed drainage system 99%, clear urinary flow 96%, urine volume under two thirds of the level of the collection bag 96% and fixation of the vesical catheter was accomplished in only 7%, implying the data of the indicator assessed. The indicators of the process are useful tools for the prevention of infection control, once it permits systematic evaluations of the interventions and consequently propositions of better structured educational strategies.